Utilization of the Potential of Mangrove Forest Areas to Increase the Income of Coastal Communities in Kipai Village, Patani District - Umaternate, Abd. Rasyid; Bau, Suharlin Ode; Mamuasi, Rahmat; Amiruddin, Usman; Dai, Fartina La Ode; Hanafi, Mujiono (LP2M INSURI Ponorogo, 2025)
Mangrove forests in Kipai Village provide significant benefits in terms of economy, ecology, and social aspects. However, the local community has limited awareness of these forests' direct and indirect benefits, particularly regarding the economic potential of mangrove-based commodities they have unknowingly utilized. This activity aims to provide training and assistance to the community, specifically to partners, on maximizing the potential of mangrove forest areas to improve the income of coastal communities in Kipai Village. Implementing this Community Service activity follows a structured approach to address partner challenges, including socialization, training, technology application, assistance, evaluation, and program sustainability. The evaluation involves interviewing several partner groups to gather feedback and impressions of the activities. The community members, particularly those who participated, have reported feeling the positive impact of the activity, as it has enhanced their knowledge and skills in utilizing the mangrove area's potential, thus enabling them to process it into products with higher economic value.